Impact of polyethylene terephthalate and polylactic acid nanoplastics on cellular uptake and lipid metabolism in differentiated 3T3-L1 adipocytes - Yu-Tung Jhang; Ching-Hao Li; Chih-En Yeh; Yen-Ju Chan; Tsung-Min Yang; Carlos Jose Quiroz Reyes; Ching-Wei Lin; I-Lun Hsiao (Ecotoxicology and Environmental Safety, 2025)
Hazards of nanoplastics (NPls) have recently garnered concern because of their tiny size and widespread existence in the environment and daily life. Evidence indicates that the frequently used model particle polystyrene NPls can accumulate in adipose tissues of mice and disrupt lipid metabolism, which is a potential obesogen. However, NPl uptake mechanisms and their potential interference with energy homeostasis of adipocytes by other NPl types are still unknown. In this study, polyethylene terephthalate (PET) and polylactic acid (PLA)–NPls which were shown to abundantly be released from plastic tea bags at brewing temperatures–were selected to study the abovementioned issues in 3T3-L1 adipocytes. We found that similar sized self-synthesized PET NPls and commercial PLA NPls could be taken up by cells, and the former’s uptake was via clathrin-mediated endocytosis and micropinocytosis, and they were then localized in lysosomes. PET NPls treatment decreased triglycerides (TGs) and increased the non-esterified fatty acid (NEFA) level. Significant activation of AMP-activated protein kinase (AMPK) and hormone-sensitive lipase (HSL) was observed. However, none of the effects was found with PLA. No representative proinflammatory factors were induced by NPl treatment. This study first proved that NPl-induced lipolysis of adipocytes is dependent on the plastic type, which serves as a basis for future concerns about NPl effects on cardiovascular disease and non-alcoholic fatty liver disease driven by adipocyte dysfunction.